Teman Ps (Teh Mangrove Posi Posi) Dalam Upaya Penyediaan Produk Cendramata Di Obyek Wisata Mangrove Guraping Kecamatan Oba Utara Kota Tidore Kepulauan - Rina; Abubakar, Salim; Subur, Riyadi; Fadel, Ariyati H.; Sunarti; Abubakar, Yuyun; Iksan, Kusdi Hi; Susanto, Adi Noman; Tahir, Imalita; Najamuddin; Achmad, M. Janib; Muksin, Darmiyati; Rumagia, Faizal; Widhi, Raut Nugrahening; Paluphi, Raut Wahyuning; Duwila, Suhartono (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
The pedada fruit (Sonneratia alba), locally known as posi-posi, has potential as a raw material for herbal tea with various health benefits, such as lowering cholesterol, relieving gout, providing antioxidant effects, reducing gastric acidity, and supporting organ health. However, mangrove tea has not yet been widely marketed in North Maluku, and it is not available as a local tourism souvenir. This Community Service Program (PKM) aimed to: (i) increase partners’ knowledge of mangrove fruit as a business opportunity, (ii) apply appropriate technology in tea processing, and (iii) produce high-quality mangrove tea variants with market value. The implementation stages included: (1) knowledge delivery through presentations and discussions, (2) mangrove exploration along the Guraping tourism tracking route, and (3) demonstration of mangrove tea processing. The product was developed into five variants: TeOry, Tebal, TeGo, TTM, and PosiNaga. Each variant was packaged in tea bags and boxes, then evaluated using hedonic organoleptic testing based on color, aroma, taste, and texture. The results indicated that mangrove tea has promising potential as a distinctive tourism souvenir and as a new business opportunity for local communities.